Design and Development of a Smart Trash Bin for Recyclable Wastes - Flores, Earl John C.; Dauz, Mark Chester; Calica, Rafael; De Guzman, Dianne Ross; Ganuelas, Joselito; Olbinado, Rommick; Ventura, Ace Benjhon (Southeast Asian Journal of Science and Technology, 2023)
Most human activities generate solid waste, which is an unavoidable byproduct. Solid waste management is critical to reducing waste and improving recycling. Uncollected trash and poor waste disposal have severe health and environmental repercussions. Furthermore, most public trash bins overflow due to inefficient waste management practices. As a result, for an immediate and optimized waste collection operation, a waste classification management and remote monitoring system are required to properly segregate trash and notify relevant authorities about the trash levels of the bins. This paper presents the design and development of a smart trash bin that uses an Arduino microcontroller to segregate recyclable materials, monitor trash levels in bins, and send an SMS alarm to authorities through GSM communication. A 12V battery powers the system, supplemented by a solar panel. The smart trash bin’s design is appropriate for proper waste disposal of recyclable materials. It will assist authorities in planning an efficient waste collection strategy. The designed trash bin costs 180 USD, which is comparable and affordable to existing smart trash bins.